2019
DOI: 10.1080/23802359.2019.1624210
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships and characterization of the complete chloroplast genome of strawberry, Fragaria x ananassa (Rosaceae: Fragaria)

Abstract: Strawberry (Fragaria x ananassa) is an economically and important fruit species that is grown extensively around the entire world. In this study, we obtained the complete chloroplast genome of F. x ananassa. The chloroplast genome of F. x ananassa is 155,529 bp in size, containing a large singlecopy region (85,523 bp), a small single-copy region (18,136 bp) and a pair of IR regions (each one of 25,935 bp). The overall GC contents of the chloroplast genome is 37.2%. The chloroplast genome of F. x ananassa conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The genome of chloroplasts has been determined for several cultivated and wild species (Bai et al, 2017;Cheng et al, 2017;Harrison et al, 1997;Honjo et al, 2009;Huang et al, 2019a;Li et al, 2021a;Song et al, 2023;Sun et al, 2021). Different types of photosynthesis-related genes respond differently to hybridisation and chromosome doubling within Fragaria .…”
Section: Photosynthesis Varies Across Strawberry Species Hybrids and ...mentioning
confidence: 99%
“…The genome of chloroplasts has been determined for several cultivated and wild species (Bai et al, 2017;Cheng et al, 2017;Harrison et al, 1997;Honjo et al, 2009;Huang et al, 2019a;Li et al, 2021a;Song et al, 2023;Sun et al, 2021). Different types of photosynthesis-related genes respond differently to hybridisation and chromosome doubling within Fragaria .…”
Section: Photosynthesis Varies Across Strawberry Species Hybrids and ...mentioning
confidence: 99%
“…Likewise cluster-III, Cluster-IV comprises members from Potentilla genus only except P. parvifolia which alone belongs to the cluster-V with other species. Similarly, the molecular phylogenetic relationship between Fragaria species and Rosaceae family were established to study the evolutionary intraspecific and interspecific relationship by using both nuclear and chloroplast sequences (Potter et al, 2000;DiMeglio et al, 2014;Huang et al, 2019). Overall the phylogenetic analysis of Rosaceae family revealed that ccsA gene sequences can be used for diversity analysis and establishment of evolutionary relationship between Rosaceae family members.…”
Section: Phylogenetic Analysismentioning
confidence: 99%